Management of Membrane Exposure Utilizing Concentrated Growth Factor (CFG) in Guided Bone Regeneration: A Clinical Report - Muhammad Syafiq Alauddin; Haslinda Ramli (BENTHAM Open, 2024)
Indexed by ERA